Bmi-1 Regulates Snail Expression and Promotes Metastasis Ability in Head and Neck Squamous Cancer-Derived ALDH1 Positive Cells. (30th August 2010) - Yu, Cheng-Chia; Lo, Wen-Liang; Chen, Yi-Wei; Huang, Pin-I; Hsu, Han-Shui; Tseng, Ling-Ming; Hung, Shih-Chieh; Kao, Shou-Yen; Chang, Charn-Jung; Chiou, Shih Hwa
Abstract : Recent studies suggest that ALDH1 is a putative marker for HNSCC-derived cancer stem cells. However, the regulation mechanisms that maintain the stemness and metastatic capability of HNSCC-ALDH 1 + cells remain unclear. Initially, HNSCC-ALDH 1 + cells from HNSCC patient showed cancer stemness properties, and high expression of Bmi1 and Snail. Functionally, tumorigenic properties of HNSCC-ALDH 1 + cells could be downregulated by knockdown of Bmi-1. Overexpression of Bmi-1 altered in expression propertyALDH 1 − cells to that ofALDH 1 + cells. Furthermore, knockdown of Bmi-1 enhanced the radiosensitivity of radiation-treated HNSCC-ALDH 1 + cells. Moreover, overexpression of Bmi-1 in HNSCC-ALDH 1 − cells increased tumor volume and number of pulmonary metastatic lesions by xenotransplant assay. Importantly, knock-down of Bmi1 in HNSCC-ALDH 1 + cells significantly decreased distant metastases in the lungs. Clinically, coexpression of Bmi-1/Snail/ALDH1 predicted the worst prognosis in HNSCC patients. Collectively, our data suggested that Bmi-1 plays a key role in regulating Snail expression and cancer stemness properties of HNSCC-ALDH 1 + cells.